Two new species of Helvella (Helvellaceae, Pezizales) from Southwestern China - Li, Tai-Shun; Yang, Yan-Yan; Yu, Feng-Ming; Li, Cui-Jin-Yi; Xu, Rong-Ju; Yang, Hu-Hua; Zhou, De-Qun; Zhao, Qi (Phytotaxa, 2025)
Species of Helvella are widely distributed in the northern temperate zone, and there are currently at least 96 phylogenetic species in China. During an investigation of discomycetous diversity in Yunnan, China, four specimens of Helvella were collected and identified as two new species, Helvella kunmingensis and H. yongpingensis, based on morphological and molecular evidences. They are similar in cupulate to discoid, greyish black apothecium, with pubescence on the receptacle surface and a developed stipe. The asci of H. kunmingensis is narrower than that of H. yongpingensis. Phylogenetic analyses of multi-locus (ITS, nrLSU, tef-1α, and hsp90) indicated that they were not related, and H. yongpingensis was closely related to H. xiaohuipan, while H. kunmingensis was sister to H. orentitomentosa. Two new species are described, illustrated, and compared with the sibling and morphologically similar species in this paper.